Analysis of Sales Transactions in Increasing Sales Promotion Using the WEKA Tool: Datamining - Lingga Wijaya, Harma Oktafia (Adpebi Science Series, 2022)
Supermarket xyz is one of the growing basic food shops in Lubuklinggau City that provides daily staples. More than 50 types of food and non-food products are available at competitive prices, meeting almost all the daily needs of consumers. With a fairly large number of transactions, xyz supermarkets need analytical tools to provide useful information for xyz supermarkets in marketing strategies, what goods are most in demand by consumers and others [1]. The problem that exists is the sales transaction data of XYZ supermarkets. has not been able to provide information about the pattern or relationship of a set of items purchased by customers. To help the algorithm process using a priori where a priori will help solve the existing stages, for mining a test is carried out with the Weka application, WEKA is a practical tool. This study processes sales transaction data as many as 1339 transactions and produces 6 best rules that can be used by XYZ Supermarkets as a marketing strategy in the future.